Budaya Tektonika dan Kearifan Lokal Rumoh Aceh dalam Mengidentifikasi Ciri Arsitektur pada Bangunan di Provinsi Aceh - Teuku Ivan; Masdar Djamaludin; Zulfikar Taqiuddin; Mirza Mirza (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2025)
Local architecture serves as an authentic representation of a society's identity, tradition, and material adaptation, which is currently being eroded by the currents of globalization and advancements in information technology. This study aims to conduct an in-depth examination of the characteristics of Rumoh Aceh as a crucial element in the history of the Acehnese people, while simultaneously evaluating the extent of the implementation of these local features in public buildings across Aceh Province. Adopting a qualitative approach, this research explores social and technical phenomena through four systematic stages: preparation, primary data collection through pure oral tradition, analysis of construction techniques, and evaluation of the built environment. The findings indicate that Rumoh Aceh possesses distinctive tectonic excellence, characterized by a nail-less joint system (using pegs and rattan ties), an orientation toward the Qibla, and a spatial configuration (Seuramoe Keue, Seuramoe Teungouh, and Seuramoe Likot) that is responsive to both climate and religious values. Although the role of the Utoh (traditional architect) and the availability of timber are diminishing, the philosophy of Rumoh Aceh remains relevant for adaptation into modern structures using concrete materials, as demonstrated by the Aceh Governor's Office and the Tsunami Museum. This study concludes that the integration of modern technological innovation with the principles of local wisdom is vital for preserving the identity of Nusantara architecture in Aceh.in buildings throughout Aceh Province.